1993
DOI: 10.2527/1993.712459x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fumonisin-contaminated corn screenings on growth and health of feeder calves

Abstract: Fumonisins are myocotoxins produced by Fusarium moniliforme and F. proliferatum, common molds of corn in North America. The toxin is at especially high concentrations in corn screenings. Fumonisins are toxic to swine and horses, but effects of these toxins in cattle have not been evaluated. This experiment was conducted to determine the effects in cattle of feeding fumonisins at levels known to be toxic to swine and horses. A total of 18 crossbred feeder calves were fed diets containing fumonisins at 15, 31, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
45
1
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 0 publications
5
45
1
3
Order By: Relevance
“…In addition, it is very important to underline the persistency of increased GGT activity after the suspension of A-F treatment, which could be considered a signal of deep damage to intrahepatic hepatobiliary ducts in the previous phase. The increase in GGT activity in A-F heifers agrees with the results by Osweiler et al (1993) and Mathur et al (2001), confirming the role of GGT as a metabolic marker for intoxication from fumonisins. In growing lambs, Edrington et al (1994) confirmed the damage caused by aflatoxins to hepatic and hepatobiliary cells function with an increase both in serum GGT and AST activities.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, it is very important to underline the persistency of increased GGT activity after the suspension of A-F treatment, which could be considered a signal of deep damage to intrahepatic hepatobiliary ducts in the previous phase. The increase in GGT activity in A-F heifers agrees with the results by Osweiler et al (1993) and Mathur et al (2001), confirming the role of GGT as a metabolic marker for intoxication from fumonisins. In growing lambs, Edrington et al (1994) confirmed the damage caused by aflatoxins to hepatic and hepatobiliary cells function with an increase both in serum GGT and AST activities.…”
Section: Discussionsupporting
confidence: 87%
“…The ALP and total bilirubin values recorded during the EP did not differ among diets probably because of the chronic kind of this challenge. This was the reason for the difference between the results obtained in our trial and those obtained by Lynch et al (1970 and1971) with AFB 1 and by Osweiler et al (1993) with FB 1 and FB 2 contaminations; in these two studies, in fact, the challenge was acute. Gelderblom et al (2001) also did not report any effect on ALP in rats, after a treatment of chronic intoxication from fumonisins.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Fumonisin (FB 1 ) is the most abundant of the fumonisins produced by F. moniliforme. The fumonisins cause encephalomalacia in horses 11 and pulmonary hypertension with pulmonary artery medial hypertrophy and right ventricular hypertrophy in swine, 4,21 are hepatotoxic in most animal species 3,[8][9][10]14,24 and carcinogenic in rats 6 and possibly people, 22 and are nephrotoxic in rats and rabbits. 8,24 Swine also exhibit altered myocardial function when exposed to fumonisins, and porcine cultured endothelium exhibits disruption of barrier function when FB 1 is present.…”
mentioning
confidence: 99%
“…7,21 Previously, cattle fed fumonisins experimentally for short periods of time to determine the effects exhibited only minimal hepatic and immune function changes. 14,15 Cattle in feed lots are fed large quantities of corn for weight gain and occasionally develop pulmonary hypertension and congestive heart failure even at altitudes that are not usually considered a risk for pulmonary hypertension. This experiment was conducted to determine if cattle develop pulmonary hypertension in response to consumption of fumonisins for prolonged periods of time at altitudes that are not usually associated with pulmonary hypertension in cattle.…”
mentioning
confidence: 99%